Application of Incoterms in Logistics - Ismailova, Madina; Halík, Jaroslav, 1961-; Štěrbová, Ludmila, 1957-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2020)
This thesis provides analytical data on how the application of Incoterms® would change the logistics system in Kazakhstan. The thesis presents theoretical and practical data on what are Incoterms®, how logistics influence country’s businesses and economy, what are other efficient tools and methods in the supply chain of companies and finally what is the current situation of logistics in Kazakhstan.
Vedoucí práce: Jaroslav Halík
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses